Variation in tube voltage for pediatric neck 64VCT: Effect on radiation dose and image quality. - Li-Guo Chen (Public Library of Science (PLoS), 2021)
Exposure to ionizing radiation can cause cancer, especially in children. In computed tomography (CT), a trade-off exists between the radiation dose and image quality. Few studies have investigated the effect of dose reduction on image quality in pediatric neck CT. We aimed to assess the effect of peak kilovoltage on the radiation dose and image quality in pediatric neck multidetector-row CT. Measurements were made using three phantoms representative of children aged 1, 5, and 10 years, with tube voltages of 80, 100, and 120 kilovoltage peak (kVp); tube current of 10, 40, 80, 120, 150, 200, and 250 mA; and exposure time = 0.5 s (pitch, 0.984:1). Radiation dose estimates were derived from the dose-length product with a 64-multidetector-row CT scanner. Images obtained from the control protocol (120 kVp) were compared with the 80- and 100-kVp protocols. The effective dose (ED) was determined for each protocol and compared with the 120-kVp protocol. Quantitative analysis entailed noise measurements by recording the standard deviation of attenuation for a circular 1-cm2 region of interest placed on homogeneous soft tissue structures in the phantom. The mean noise of the various kVp protocols was compared using the unpaired Student t-test. Reduction of ED was 37.58% and 68.58% for neck CT with 100 kVp and 80 kVp, respectively. The image noise level increased with the decrease in peak kilovoltage. Noise values were higher at 80 kVp at all neck levels, but did not increase at 100 kVp, compared to 120 kVp in the three phantoms. The measured noise difference was the greatest at 80 kVp (absolute increases<2.5 HU). The subjective image quality did not differ among the protocols. Thus, reducing voltage from 120 to 80 kVp for neck CT may achieve ED reduction of 68.58%, without compromising image quality.